Coastal Community Empowerment through Joint Venture (Study of PT Badak NGL) - Busori Sunaryo; Bambang Eko; Reta Yudistyana (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2019)
The government is currently trying to realize Sustainable Development Goals/ SGDs. SGDs are not merely dreams that cannot be realized. The noble goal of SDG is to realize sustainable development for the better future that is in line with the concepts of CSR (Corporate Social Responsibility). One of the companies that participated in the realization of SDGS is PT Badak NGL. This study used descriptive analysis to provide clear descriptions or overviews of the object of the study. The study also used a case study of a MSME under the guidance of PT Badak NGL, namely Saputra Snack. Thus, the common goals between CSR, and SDGs is the spirit to realize sustainable development in terms of business strategies by implementing CSR programs. If all elements are committed to realize 17 SDG, so we can provide better future for our children - with low poverty, environment and earth sustainability, low levels of inequality in the economic, social and legal education sectors. Based on the observation and analysis, one of the keys of success to Saputra Snack was its high commitment. The high commitment did not only come from Saputra Snack itself, but also from PT Badak NGL Community Development party.